2017
DOI: 10.1002/rcm.7883
|View full text |Cite
|
Sign up to set email alerts
|

New cascarosides from Rhamnus purshiana and fragmentation studies of the class by ion trap mass spectrometry

Abstract: The proposed fragmentation patterns can be used to differentiate anthrones from oxanthrones in both ion modes. In addition, they can be applied to differentiate these compounds in anthraquinone-rich plants and phytotherapic drugs. Finally, herein, the strategy applied allowed us to identify new natural products. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…11 Based on a thorough conformational analysis including molecular dynamic simulations, we briefly confirm the validity of the NMR-and ECD-spectroscopic approaches for the determination of the AC at C 10 . 11 Based on a thorough conformational analysis including molecular dynamic simulations, we briefly confirm the validity of the NMR-and ECD-spectroscopic approaches for the determination of the AC at C 10 .…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…11 Based on a thorough conformational analysis including molecular dynamic simulations, we briefly confirm the validity of the NMR-and ECD-spectroscopic approaches for the determination of the AC at C 10 . 11 Based on a thorough conformational analysis including molecular dynamic simulations, we briefly confirm the validity of the NMR-and ECD-spectroscopic approaches for the determination of the AC at C 10 .…”
Section: Introductionmentioning
confidence: 53%
“…In this contribution, we revisit the important stereochemistry at C 10 of the cascarosides A, B, and C (1-3), as well as of the only very recently isolated and characterized 10-hydroxy-cascarosides A and B (4 and 5). 11 Based on a thorough conformational analysis including molecular dynamic simulations, we briefly confirm the validity of the NMR-and ECD-spectroscopic approaches for the determination of the AC at C 10 . Furthermore, we discuss the results of a VCD spectroscopic characterization of these five compounds, which allow us to establish another set of empirical spectra-structure correlations for the class of (ox-)anthrones.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Phytochemical studies have demonstrated that anthraquinone diglucosides, namely, cascarosides A–F, are the characteristic constituents of cascara sagrada and that cascarosides A and B, especially, are the main anthraquinone glycosides while cacarosides C–F are the relatively minor ones [8–11]. Concerning the chemical structures of the cascarosides, the aglycones of cascarosides A–F were classified into three groups: the aloe‐emodin (cascarosides A and B), chrysophanol (cascarosides C and D), and emodin (cascarosides E and F) types, and two glucosyl moieties, 8‐ C‐ glucose and 10‐ O‐ glucose (Figure 1), were linked to each aglycone.…”
Section: Introductionmentioning
confidence: 99%